Motivation structure of women in the first mature age to physical culture-improving activity - Bibik R.V; Goncharova N.N; Habinets T.A (Kharkov National Pedagogical University, 2010)
Information is generalized about the different going near the analysis of reasons athletic-health-improvement employments. Research of reasons of employments of women of the first mature age is conducted by health activity. 94 women took part in an experiment. Priority reasons and directions of their perfection are certain. An estimation is given to the observance of bases of women healthy way of life. Importance of account of reasons is lighted up at the construction of health employments of women. Reasons of insufficient orientation of women are selected on a health and conduct of healthy way of life.